Assessing Without Words: Verbally Incomplete Utterances in Complaints - Skogmyr Marian, Klara (Frontiers in Psychology, 2021)
This study investigates the use of verbally incomplete utterances in French-language complaints about third parties or states of affairs. In these cases, a speaker initiates a turn with verbal means but stops talking before reaching lexico-syntactic completion. The utterance becomes recognizable as an expression of negative stance or as a precise negative assessment by virtue of the linguistic formatting of the turn-initiation, its position within the larger interactional context, and the speaker’s accompanying bodily-visual displays and vocalizations. Data consist of video-recorded coffee-break conversations among first and second language speakers of French. Using multimodal Conversation Analysis, the analysis documents recurrent linguistic formats of the verbally incomplete utterances and examines the interactional deployment of the utterances in two distinct sequential contexts: (1) in the initiation of complaints, and (2) at the end of complaint tellings or reports. In the first of these, the action of leaving a turn verbally incomplete and expressing stance with bodily-visual means allows the speaker to prepare the grounds for the complaint by foreshadowing the negative valence of the upcoming talk. In the latter case, the verbally incomplete utterance and accompanying vocal and/or embodied conduct are deployed as a summary assessment or upshot of the complaint which shows, rather than merely describes, the complaint-worthiness of the situation. In both cases, the utterances work to enhance the chances for the speaker to obtain affiliative responses from coparticipants. While prior studies on verbally incomplete utterances have suggested that such utterances may be specifically suitable for subtly dealing with delicate actions, in this study the utterances are sometimes produced as part of multimodal ‘extreme-case expressions’ that convey negative stance in a high-grade manner. The findings contribute to a better understanding of interactional uses of verbally incomplete utterances and of the multimodal nature of negative assessments. The study thereby furthers our understanding of how grammar and the body interface as resources for the accomplishment of context-specific actions and the organization of social interaction.